Online shopping Experience and Repeat Purchase: Empirical Evidence from Students of Imam Mohammad Ibn Saud Islamic University, Saudi Arabia - Al-khateeb, Bilal Ahmad Ali (Journal of Posthumanism, 2025)
Nowadays, technologies have altered change way people shop across the world, especially through the internet. Online shopping represents one of these ways, offering people now opportunities for people to make purchases online from home. However, their initial experiences of shopping online appear to affect repeat purchases which is a major concern for the online shop owners. This study investigates the online shopping experience and repeats purchase among the Imam Mohammad Ibn Saud Islamic University (IMSIU) students in Saudi Arabia. The study adopted a survey questionnaire design. The population covered all the students of IMSIU, however, only those who have previous online shopping experience were finally included in the study. A snowballing sampling technique was used to select those who finally participated in the study. The sample size in all is 227 students (online shoppers) of IMSIU. It made use of primary data which is a survey questionnaire. Data collection was conducted through an email survey procedure. The collected data was analysed using both SPSS and Stata were it was found that online shopping experience is statistically significantly related to repeat purchase among the students of IMSIU. On the other hand, the correlation results revealed that online shopping experience has a low negative correlation with repeat purchase among the participants. An additional probe revealed that neither gender nor age brings about online repeat purchase among the participants. The study therefore concludes that online shopping experience significantly but negatively affects repeat purchase among the students in IMSIU. The discussion for findings, implication, limitations including suggestion for studies are provided.